Synthesis and characterisation of ionic mixed copper (ll) carboxylate complexes, K[n][Cu[2](p-OC[6]H[4]COO)[n](RCOO)[4]-[n\] as thermally stable solar cell materials / Lailatun Nazirah bt Ozair - Ozair, Lailatun Nazirah (2012)
The objective of this research was to synthesise and characterize stable low-temperature ionic copper(II) mixed carboxylates as hybrid heat-light solar-cell materials. Their general formula is Kn[Cu2(p-OC6H4COO)n(RCOO)4-n], where n = 1-3, and R = saturated or unsaturated alkyl group. Two methods were used to prepare these complexes: one-pot and ligand-exchange reactions. The complexes were analysed by CHN elemental analyses, FTIR spectroscopy, UV-vis spectroscopy (solid and solution), TGA, DSC, room-temperature magnetic susceptibility, cyclic voltammetry (CV), and for suitable complexes, by photoluminescence spectroscopy (PL). Crystalline complexes were analysed by single-crystal X-ray crystallography. The one-pot reaction was successfully used to prepare five ionic dinuclear copper(II) mixed-carboxylates. All complexes were square pyramidal at Cu(II) centre(s). The binding mode of the carboxylate ligand was either syn-syn or syn-anti bridging and/or chelating. Their optical band gap energy and thermal stabilities range from 2.89 eV to 3.11 eV, and from 175 to 817 oC, respectively. All dinuclear complexes were antiferromagnetic and showed quasireversible redox properties. The ligand-exchange reaction was successfully used to prepare six ionic precursor complexes of general formula [Cu2(p-HOC6H4COO)(RCOO)3], where R is CH3CH=CH,CH3(CH2)7CH=CH(CH2)7, (CH3)3C, CH3(CH2)3CH(CH2CH3) and CH3(CH2)7CH(CH2). These complexes were either tetrahedral or square pyramidal at Cu(II) centre(s). The binding mode of the carboxylate ligand was either syn-syn bridging or monodentate and chelating. Their optical band gap energy and thermal stability range from 2.18 eV to 2.63 eV and from 170 to 225oC, respectively. The square pyramidal complexes were antiferromagnetic, while the tetrahedral complex was ferromagnetic. All complexes showed quasireversible redox properties. [Cu2(p-HOC6H4COO)(CH3(CH2)7CH=CH(CH2)7COO)3] was not successfully converted to K[Cu2(p-OC6H4COO)(CH3(CH2)7CH=CH(CH2)7COO)3], using KOH. Eight of the above complexes showed photoluminescence properties when excited at 267 nm (intraligand n!π* electronic transition) or 325 nm (LMCT electronic transition). The chemical formulas of these complexes are: •K[Cu(CH3CH=CHCOO)(OH)2(H2O)].H2O •K2[Cu2(p-OC6H4COO)2(CH3CH=CHCOO)2(H2O)2] •K[Cu2(p-OC6H4COO)(CH3CH=CHCOO)3(CH3CH2OH)2] •K[Cu2(p-OC6H4COO)(CH3CH=CHCOO)3].2H2O •K[Cu2(p-OC6H4COO)(CH2=C(CH3)COO)3(CH3CH2OH (CH2=C(CH3)COOH)] •K3[Cu2(p-OC6H4COO)3(CH2=C(CH3)COO)(CH3CH2OH)2].H2O •[Cu2(p-HOC6H4COO)3(CH3CH=CHCOO)(C5H5N)].C5H5N •[Cu2(p-HOC6H4COO)(CH3(CH2)7CH((CH2)5CH3)COO)3(H2O)2] All complexes have an emission peak at about 550 nm, and therefore are potential solar materials as they were able to capture and trap the photonic energy corresponding to MLCT transition.